Study on the Preparation and Antioxidant Property of Amaranthus Paniculatus L. incorporated biomass composite fiber. (2019) - Tang, Wenying; Li, Yajing; Yin, Xueqian; Shi, Yidong; Zhang, Yong; Sun, Hui; Tan, Lin
Abstract: Nowadays, functional and smart fibers have been extensively studied worldwide, and the research in developing sustainable fibers involved with natural plant is still in the early stage. Amaranthus Paniculatus L . (APL) is a natural annual plant which possesses strong growth ability. In present study, we aim to comprehensively develop and utilize APL, and successfully fabricated a series of "green" and functional composite fibers consisting of APL superfine power, TPU and PAN through wet-spinning technology. The resultant fibers were characterized in terms of mechanical properties, morphologies and thermal stabilities. Furthermore, the desirable antioxidant activity with around 30% DPPH free radical scavenging rate was demonstrated. Therefore, we believe that the present study can pave a way to make full use of natural plant and fulfilling the possibility of transferring waste to valuable products.